Laboratory measurement of relative permeabilities of oil and water in sand - Naweed Seddiqi, Khwaja; Mahdi, Zabihullah; Honma, Shigeo (Scientific Journal of Environmental Sciences, 2016)
The relative permeability of two immiscible fluids in sand is measured in the laboratory based on the steady-state method. Three sorts of oils, Kerosene, heavy oil and lubricant oil, and water are pumped simultaneously into a vertical sand column with different pumping ratio. From the change in fractional discharge measured at the outlet, a method for determining the relative permeability is developed focusing on the displacement mechanism in sand. Two sorts of experiments, one is the displacement of pore water by oil, the other is the displacement of pore oil by water, are carried out. It is revealed that the relative permeability curves display tolerably different shape owing to the kinds of oils, and produce different amount of residual oils. For the design of the waterflooding technique to predict the oil recovery in petroleum reservoir, it is necessary to asses the relative permeability of the reservoir oil taking care of their characteristics.